Strategi Guru Dalam Meningkatkan Kemampuan Menghafal Surah-Surah Pendek pada Mata Pelajaran Al-Quran Hadist Siswa Kelas Rendah MI - Nurul Huda (Madrasah: Jurnal Pendidikan Madrasah, 2025)
This study aims to describe teacher strategies in improving memorization of short surahs in the Al-Quran Hadith subject for grades 2 and 3 at MIS Ummul Qura. The method used in this study is a qualitative method. The subjects of this study were teachers of grades 2 and 3 of the Al-Quran Hadith subject. Data collection techniques used interviews, observation, and documentation. While data analysis used data reduction, data presentation and verification. The results of the study show that there are 3 main strategies of Al-Quran Hadith teachers for grades 2 and 3 in improving memorization of short surahs. First, a good understanding of the characteristics, abilities and learning styles of students. Knowledge of student differences (abilities, characteristics, learning styles) plays an important role in designing effective, efficient learning, and all student differences can be facilitated well. Second, the selection and use of appropriate and relevant learning methods. The methods used include tasmi', talaqqi, tikrar, wahdah. Third, giving rewards for students' success in memorizing short surahs. The rewards given by teachers in learning the Al-Quran and Hadith for grades 2 and 3 are in the form of praise, stars and certificates.